Measurements of Intra- and Extra-Cellular 5-Methyltetrahydrofolate Indicate that Bifidobacterium Adolescentis DSM 20083T and Bifidobacterium Pseudocatenulatum DSM 20438T Do Not Actively Excrete 5-Methyltetrahydrofolate In vitro - Kopp, Markus; Dürr, Kerstin; Steigleder, Matthias; Clavel, Thomas; Rychlik, Michael (Frontiers in Microbiology, 2017)
Certain intestinal bifidobacteria have the ability to synthesize folates. In vitro experiments revealed a high production, cellular accumulation, and release of reduced folate vitamers like 5-methyltetrahydrofolate and tetrahydrofolate in folate-free medium (FFM). However, it is still unclear to which extent synthesized folates are polyglutamylated and probably not available for transport, and if they are actively released by excretion. To address these questions, we characterized intra- and extracellular pteroylmonoglutamates and polyglutamylated 5-methyltetrahydrofolate (5-CH3-H4PteGlu2-4) in B. adolescentis DSM 20083T and B. pseudocatenulatum DSM 20438T in vitro. Folates were measured by means of stable isotope dilution assays coupled with LC-MS/MS analysis using [2H4]-5-methyltetrahydrofolic acid, [2H4]-tetrahydrofolic acid and [2H4]-5-formyltetrahydrofolic acid as internal standards. Cell viability was examined by fluorescence microscopy. Quantitation of folate production by B. adolescentis during the stationary phase revealed a linear increase of dead cells paralleled by increasing concentration of 5-formyltetrahydrofolate and 5-methyltetrahydrofolate (100% 5-CH3-H4PteGlu4) in FFM, whereas the intracellular concentrations of these vitamers remained constant. After 24 h, B. adolescentis (125 mg cells, wet weight) produced a total amount of 0.846 nmol 5-CH3-H4folate: 0.385±0.059 nmol (46±7%) and 0.461±0.095 nmol (54±11%) measured in the intracellular (viable cells; 52±3% measured by fluorescence microscopy) and extracellular (lysed cells; 48±3%) fraction, respectively. For B. pseudocatenulatum (124 mg cells, wet weight), 1.135 nmol 5-CH3-H4folate was produced after 24 h, and a similar proportionality between intra/extracellular folate concentrations and viable/lysed cells was observed. These results indicate that the strains tested produce and accumulate 5-CH3-H4PteGlu4 for cellular metabolism, and that extracellular concentrations of the vitamer arise from cell lysis.